Relationship between device‐detected subclinical atrial fibrillation and heart failure in patients with cardiac resynchronization therapy defibrillator - Arai, Shuhei (Clin Cardiol, 2020)
BACKGROUND: Atrial fibrillation (AF) is a leading preventable cause of heart failure (HF) for which early detection and treatment is critical. Subclinical‐AF is likely to go untreated in the routine care of patients with cardiac resynchronization therapy defibrillator (CRT‐D). HYPOTHESIS: The hypothesis of our study is that subclinical‐AF is associated with HF hospitalization and increasing an inappropriate therapy. METHODS: We investigated 153 patients with an ejection fraction less than 35%. We divided into three groups, subclinical‐AF (n = 30), clinical‐AF (n = 45) and no‐AF (n = 78). We compared the baseline characteristics, HF hospitalization, and device therapy among three groups. The follow‐up period was 50 months after classification of the groups. RESULTS: The average age was 66 ± 15 years and the average ejection fraction was 26 ± 8%. Inappropriate therapy and biventricular pacing were significantly different between subclinical‐AF and other groups (inappropriate therapy: subclinical‐AF 13% vs clinical‐AF 8.9% vs no‐AF 7.7%: P = .04, biventricular pacing: subclinical‐AF 81% vs clinical‐AF 85% vs no‐AF 94%, P = .001). Using Kaplan‐Meier method, subclinical‐AF group had a significantly higher HF hospitalization rate as compared with other groups. (subclinical‐AF 70% vs clinical‐AF 49% vs no‐AF 38%, log‐rank: P = .03). In multivariable analysis, subclinical‐AF was a predictor of HF hospitalization. CONCLUSIONS: Subclinical‐AF after CRT‐D implantation was associated with a significantly increased risk of HF hospitalization. The loss of the biventricular pacing and increasing an inappropriate therapy might affect the risk of HF hospitalization.